Análisis de los factores de capital humano en la Cooperativa de Ahorro y Crédito CACPECO Ltda. Agencia La Maná. - Nuñez Zambrano, Chris Salma (2024)
The research project "Analysis of human capital factors at the Cooperativa de Ahorro y Crédito Cacpeco Ltda. La Maná agency" is focused on identifying the human capital factors related to the credit cooperative which is located in La Maná canton, Cotopaxi province. The research was sponsored by the Faculty of Administrative Sciences, specifically by the Business Administration Major. The objective of the study was to analyze the human capital factors and which of these factors were presented in the entity by taking into account the 14 employees of the cooperative as beneficiaries who are the ones who make up the human capital. The studied human capital factors included “knowledge” that integrates the training and education of employees and their experience in the financial sector, the “shared values” which are the commitment to the mission and values of the cooperative, the “ work skills” being the ability to work as a team and dedication to customer service, followed by “work environment and compliance” being the place in which daily work activities are carried out, “psychological and social motivations” with the purpose of understand what the greatest motivators are, and finally “health and well-being” which is one of the factors that is aimed at understanding if the work is beneficial in terms of health. The obtained results from the surveys revealed gaps in financial, credit, and technical knowledge among employees, as well as the lack of identification with the values and principles of the cooperative, so affecting employee commitment. Furthermore, the application of Exploratory Factor Analysis (EFA) suggested main components and questions that provided insights into the most relevant factors of human capital in the cooperative. It showed that some of the components in the application do not belong to any of the factors that were initially analyzed. The diagnosis revealed challenges in adequate training, employee commitment and talent retention which are considered crucial for the improvement of the cooperative. These findings provide a solid basis for future actions and improvements in human capital management in the cooperative.